17 - Anti-Aids Drugs in South Africa: An Argument for Global Community: Caroline G. Redding - Caroline G. Redding, (CODESRIA Bulletin, 2003)
In recent years the issue of how to provide Aids drugs to developing countries has been brought to the forefront of international and domestic debate. This issue is of particular importance to sub-Saharan Africa as Aids rates spiral out of control, threatening to bust the budgets of the fragile and underdeveloped health care systems of some of the poorest countries in the world. The Aids drugs debate has drawn a great deal of attention from a variety of constituencies, including pharmaceutical multinational corporations, national governments, international organisations and non-governmental organisations. The most notable result of the debate has been the apparent creation of a new global community. Comprised of various advocacy groups and individuals this community has taken the Aids drugs debate beyond the traditional Westphalian model of nation state interaction and created a model for global participatory democracy.